The effect of big five personality on student engagement in high school student at Yogyakarta - Azizah, Fathina; Setiawati, Farida Agus (Psychological Research and Intervention, 2022)
The low level of student engagement happened when the pandemic COVID-19 with dynamic learning system changes. The changes in the learning system from distance learning, and restricted face-to-face learning, to complete face-to-face learning, made student must be adaptive. A student's ability to maintain student engagement can't be taken off from the student's personality. Therefore, this study aims to determine the effect of Big Five Personality on student engagement in high school students in Yogyakarta. This study used a quantitative approach with ex post facto type. Participants involved in this study as many as 349 students from high schools located in Yogyakarta. This study's instruments were the student engagement scale and Big Five Inventory. The data analysis technique used multiple linear regression. The results of this study showed that there was a positive influence of Big Five Personality on student engagement with Sig. 0.000 (p<0.05) and the effective contribution is 27,2%. Personality traits that specifically influence student engagement are agreeableness (Sig.=0.045), conscientiousness (Sig.=0.00), and openness (Sig.=0.006). Every personality trait had an effective contribution with extraversion as much as 4,35%, agreeableness as much as -0,02%, conscientiousness as much as 16,96%, neuroticism as much as 0,2%, dan openness as much as 5,73%.